2023
DOI: 10.1002/ijgo.14638
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum deceleration and acceleration areas are associated with neonatal encephalopathy

Abstract: Objective To investigate whether an association exists between deceleration and acceleration areas on continuous fetal cardiotocography (CTG) and neonatal encephalopathy (NE). Methods A single center, retrospective case–control study was conducted to compare CTG characteristics of low‐risk pregnancies (35 weeks of gestation or more), complicated by moderate to severe NE with two matched controls for every case. Controls were matched by gestational age and cord blood pH. We analyzed the intrapartum CTG recordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…19 Nonetheless, DA and DC remain promising, objective predictors for intrapartum compromise. [8][9][10]14,16,17,58 Additional biomarkers may help improve their utility. For example, we have previously shown that hypoxaemic fetuses developed a significantly greater rise in T/QRS ratio during repeated UCOs, 47 suggesting that it may be complementary to DA and/or DC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…19 Nonetheless, DA and DC remain promising, objective predictors for intrapartum compromise. [8][9][10]14,16,17,58 Additional biomarkers may help improve their utility. For example, we have previously shown that hypoxaemic fetuses developed a significantly greater rise in T/QRS ratio during repeated UCOs, 47 suggesting that it may be complementary to DA and/or DC.…”
Section: Discussionmentioning
confidence: 99%
“…Deceleration area predicted neonatal acidaemia in large retrospective 8 and prospective cohorts 9 . Further, DA was more predictive of acidaemia than fetal heart rate (FHR) variability or numbers of late decelerations, 14 and of neonatal encephalopathy in recent retrospective cohort studies 16 . The computational index DC predicted both fetal acidaemia and neonatal compromise in a cohort of 22 790 births 10 and predicted acidaemia better than short‐term variation 13 .…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations